Efficiency of the protection system and treatment of the soil against harmful organisms in the maize crops for grain - О. V. SNIZHOK (Передгірне та гірське землеробство і тваринництво, 2021)
In recent years, there has been an annual deterioration in the phytosanitary condition of crops. One of the main factors of this phenomenon was the destabilization of the land use system and the disturbance or absence of crop rotations, which led to a high potential soil contamination by weeds and the accumulation of pests and diseases.